Chemical, Morphological and Bacterial Adhesion Analysis of Orthodontic Wires Composed of Different Metallic Alloys - Braga, Maria Leticia Lopes Miguel; Ferraz-Facury, Analia Gabriella Borges; Franco, Eduardo Martinelli; Marcelino, Larissa; Menezes, Luan dos Santos; Costa, Ana Rosa; Neves, José Guilherme (ARCHIVES OF HEALTH INVESTIGATION, 2023)
The purpose of this study was to evaluate the chemical, morphological and bacterial adhesion characteristics of orthodontic arches composed of different metal alloys. The wire segments (n=10) were allocated to the following groups: G1) Tru-Chrome- Rock Mountain Steel Wire (Colorado-USA); G2) NiTi- Rock Mountain Wire (Colorado-USA); G3) TiMb Rock Mountain Wire (Colored-USA); G4) NbTi Gummetal- Rock Mountain Wire (Colorado-USA). The orthodontic arches were segmented (20mm) and sterilized by means of ultraviolet light. Using Confocal Laser Microscopy (CLM), the roughness of archwires were investigated. The metallic alloys composition was analyzed by means of Scanning Electron Microscopy/Energy-dispersive Spectroscopy (SEM/EDS). The S. mutans biofilm growth was performed on the arches and analyzed by means of SEM and Spectrophotometry. Surface roughness and Spectrophotometry data were submitted to one-way ANOVA, followed by Tukey's test (α=0.05) and SEM/EDS data obtained by exploratory analysis. The NbTi arches showed higher surface roughness when compared to the other groups, followed by the NiTi and TiMb arches and the steel arches group (p<0.05). It was observed a lower adherence of S. mutans biofilm in steel arches when compared to the other groups. The absorbance results showed higher biofilm formation for the NbTi group, followed by Steel, NiTi and TiMb. (p<0.05). The results of EDS confirm the compositions proposed by the manufacturer. It was concluded that the alloy type in orthodontic arches has an effect on surface roughness. The chemical and morphological characteristics of the arches are related to the adhesion of S. mutans biofilm.